In Vivo Pharmacodynamic Imaging of Proteasome Inhibition - Erin A. Kimbrel; Tina N. Davis; James E. Bradner; Andrew L. Kung (Molecular Imaging)
Inhibiting the proteolytic activity of the 26S proteasome has been shown to have selective apoptotic effects on cancer cells and to be clinically efficacious in certain malignancies. There is an unmet medical need for additional proteasome inhibitors, and their development will be facilitated by surrogate markers of proteasome function. Toward this end, ectopic fusion of the destruction domain from ornithine decarboxylase (ODC) to reporter proteins is often used for assessing proteasome function. For luciferase-based reporters, we hypothesized that the oxygen-dependent destruction domain (ODD) from hypoxia-inducible factor 1α (HIF-1α) may provide improved sensitivity over luciferase-ODC, owing to its extremely rapid turnover by the proteasome (HIF-1α has a half-life of less than 5 minutes). In the current study, we show that ODD-luciferase affords a greater dynamic range and faster kinetics than luciferase-ODC in sensing proteasome inhibition in vitro. Importantly, ODD-luciferase also serves as an effective in vivo marker of proteasome function in xenograft tumor models, with inhibition being detected by noninvasive imaging within 3 hours of bortezomib administration. These data establish ODD-luciferase as a surrogate marker of proteasome function that can be used both in vitro and in vivo for the development of novel proteasome inhibitors.